Validation of lower body negative pressure as an experimental model of hemorrhage - Hinojosa-Laborde, Carmen (American Physiological Society, 2013)
Lower body negative pressure (LBNP), a model of hemorrhage (Hem), shifts blood to the legs and elicits central hypovolemia. This study compared responses to LBNP and actual Hem in sedated baboons. Arterial pressure, pulse pressure (PP), central venous pressure (CVP), heart rate, stroke volume (SV), and +dP/dt were measured. Hem steps were 6.25%, 12.5%, 18.75%, and 25% of total estimated blood volume. Shed blood was returned, and 4 wk after Hem, the same animals were subjected to four LBNP levels which elicited equivalent changes in PP and CVP observed during Hem. Blood gases, hematocrit (Hct), hemoglobin (Hb), plasma renin activity (PRA), vasopressin (AVP), epinephrine (EPI), and norepinephrine (NE) were measured at baseline and maximum Hem or LBNP. LBNP levels matched with 6.25%, 12.5%, 18.75%, and 25% hemorrhage were −22 ± 6, −41 ± 7, −54 ± 10, and −71 ± 7 mmHg, respectively (mean ± SD). Hemodynamic responses to Hem and LBNP were similar. SV decreased linearly such that 25% Hem and matching LBNP caused a 50% reduction in SV. Hem caused a decrease in Hct, Hb, and central venous oxygen saturation (ScvO(2)). In contrast, LBNP increased Hct and Hb, while ScvO(2) remained unchanged. Hem caused greater elevations in AVP and NE than LBNP, while PRA, EPI, and other hematologic indexes did not differ between studies. These results indicate that while LBNP does not elicit the same effect on blood cell loss as Hem, LBNP mimics the integrative cardiovascular response to Hem, and validates the use of LBNP as an experimental model of central hypovolemia associated with Hem.